Companion Publication of the 2021 Conference on Computer Supported Cooperative Work and Social Computing 2021
DOI: 10.1145/3462204.3481765
|View full text |Cite
|
Sign up to set email alerts
|

Listening Together while Apart: Intergenerational Music Listening

Abstract: Collaborative music listening can support intergenerational connectedness. We conducted an environmental scan of video conferencing and music listening platforms and cognitive walkthroughs to investigate how these platforms can support collaborative music listening and conversation between a grandparent and teen grandchild. Our results indicate that common video conferencing platforms not only lack a convenient way to share music, but typically block audio from music listening apps played on the same device, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Technology struggles as social opportunities Chowdhury et al (Chowdhury et al, 2021) identified how video conferencing and music listening platforms separately cannot support music colistening online. Kleinberger et al (Kleinberger et al, 2019) discussed concerns regarding technological barriers between grandparents and grandchildren and how such barriers can disrupt intergenerational interaction.…”
Section: Co-listening Supports Positive Intergenerational Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology struggles as social opportunities Chowdhury et al (Chowdhury et al, 2021) identified how video conferencing and music listening platforms separately cannot support music colistening online. Kleinberger et al (Kleinberger et al, 2019) discussed concerns regarding technological barriers between grandparents and grandchildren and how such barriers can disrupt intergenerational interaction.…”
Section: Co-listening Supports Positive Intergenerational Interactionmentioning
confidence: 99%
“…However, these are typically designed for work (e.g., Zoom, Skype), or on-demand video conferencing (e.g., FaceTime), and there is room for features to explicitly support the kinds of rich recreational features that can promote sustained interactions. While it is possible to appropriate video conferencing software and then use screen sharing and other online applications for online co-recreation, this requires a lot of tinkering on both ends of the communication channel (Chowdhury et al, 2021), which could be a barrier for many users.…”
Section: Introductionmentioning
confidence: 99%